Laser ablation microscopy reveals apical notch, apical dominance, and meristem regeneration dynamics in Marchantia polymorpha - Alan O. Marron (Proceedings of the National Academy of Sciences, 2026)
Meristems are the growth centers of plants and fundamental in understanding plant development, morphogenesis, and vegetative propagation. Across all plant groups, the phytohormone auxin controls meristem maintenance, represses the emergence of new meristems (apical dominance), and mediates cellular reprogramming when new meristems regenerate following removal of existing meristems. The liverwort Marchantia produces clonal propagules (gemmae) featuring two apical notches that develop into functional meristems. This presents a tractable experimental system to study meristem developmental biology. I used laser ablation microscopy to precisely disrupt cells in and around the developing premeristem in the apical notches of germinating gemma, finding that the first cell row is indispensable. Within this layer, a contiguous quorum of stem cells is required for activity. Apical notches reorientate in response to damage, demonstrating that the apical notch stem cells act as a communicating population. Feedback from the stem cell population is necessary to maintain notch activity and generate the notch apex. These experiments show communication between notches and regenerating meristems. The apical dominance signal represses cell division and requires both sources and sinks, features of auxin-mediated communication. Central regions of the gemma could transmit these apical dominance signals, but the tissues of the gemma periphery could not. I present a model of Marchantia gemma and apical notch organization, involving intra-, inter-, and extranotch communication. This provides a framework for further study of meristem formation, communication, and maintenance in Marchantia and improving knowledge of plant meristems more generally.